Intracellular localization of a photosensitizer and chloride channel activation in electrocytes - Santiago, Julio (2003)
The intracellular localization of a lipophilic alkyl long-chain tetraphenylporphyrin in electrocytes, Psammobatis extenta (Rajidae) is described. In contrast to the usual case, this porphyrin derivative was localized in electromotor nerves and in nuclei chromatin of electrocytes. Both structures exhibited intense fluorescence. However, the mitochondria were slightly fluorescent. These data are discussed in relation to electrocyte death in a weak electric fish. Additionally, the electron probe X-ray microanalysis suggest the activation of the chloride and cationic channels.